The Effect of Service Quality, Price, and Emosional on Customer Satisfaction at Lady Beauty Salon - Tirtayasya, Tirtayasya; Elizabeth, Sri Megawati (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the partial and simultaneous influence of service quality, price, and emotional factors on customer satisfaction at Lady Beauty Salon. The research sample consists of 118 respondents, collected using a Likert-scale questionnaire. The study employs a quantitative approach with a simple random sampling technique. The results indicate that both partially and simultaneously, service quality, price, and emotional factors have a significant influence on customer satisfaction at Lady Beauty Salon.